The Impact of Implementing Artificial Intelligence on Improving Managerial Accounting Methods Through Digital Governance: (Al-Farooq Journal of Sciences, 2026)
This study explores the integration of Artificial Intelligence (AI) as a driver for enhancing managerial accounting practices, with digital governance serving as a mediating factor. Conducted at Sahary Bank in Tripoli, the research utilizes a descriptive-analytical methodology to examine the interplay between these variables. Data were gathered through a structured questionnaire administered to a sample of 103 bank professionals and analyzed using SPSS to identify significant correlations and impacts. The findings highlight that the application of the Balanced Scorecard is pivotal for the bank, as it effectively aligns strategic goals with performance indicators. This approach successfully creates a synergy between profitability, customer satisfaction, operational efficiency, and intellectual capital growth. Crucially, the study demonstrates that these AI-supported accounting practices enable more precise and rational allocation of financial resources and liquidity toward high-growth branches. In light of these conclusions, the study emphasizes the strategic necessity of scaling up the use of expert systems. It recommends continuous investment in updating these systems with emerging knowledge to maintain operational excellence and bolster the bank’s resilience and competitive edge in complex risk management environments.
Keywords: rtificial Intelligence, Managerial Accounting, Digital Governance